Imbalanced Dermic Microbiome Aggravates Inflammation in Toenail Paronychia - Li, Ying; Ma, Han; Xue, Liang; Chen, Huizhen; Pang, Rui; Shang, Yanyan; Luo, Juan; Xie, Xinqiang; Zhang, Jumei; Ding, Yu; Chen, Moutong; Wang, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The commensal microbiome profoundly influences skin immunity but its function in toenail health remains unclear. Paronychia is one of the most common inflammatory toenail diseases, but antibiotic treatment seldom takes effect in clinical cases. In this study, we applied 16S rRNA sequencing techniques to investigate the microbial characteristics in paronychia, in order to identify the key microorganisms involved in inflammation. Seventy dermic samples were collected from paronychia patients and the dermic microbiota differences were analyzed in patients with different inflammation severities. Distinct clustering of dermal microbiota was observed in the dermis with different severities. Higher relative abundances of anaerobic microorganisms such as Parvimona, Prevotella, and Peptoniphilus were observed in severe paronychia, whereas Lactobacillus disappeared along with disease progression. Co-occurring network analysis suggested that disturbance of the dermic microbiome and attenuation of antagonism by Lactobacillus against anaerobic pathogens might have aggravated inflammation in paronychia. Functional analysis showed that dermic microbiome disturbance may worsen the microbial metabolism and tissue repair in the skin. In conclusion, our research discovered increase of anaerobic microorganisms and loss of Lactobacillus in the dermis may promote the progression of paronychia and microbiological unbalance may aggravate inflammation in patients with paronychia.